HEALTH RISK ASSESSMENT ASSOCIATED WITH NITROGEN COMPOUNDS CONTAMINATED DRINKING WATER IN MEDIAS REGION - RESZ (HOAGHIA), Maria-Alexandra; ANDREI, Mariana Lucia; CADAR, Oana; SENILA, Lacrimioara; LEVEI, Erika; RISTOIU, Dumitru (Studia Universitatis Babeș-Bolyai Chemia, 2016)
High concentrations of nitrogen compounds in drinking water may cause negative health effects. The aim of the present study was to assess the content of nitrogen compounds namely, nitrates, nitrites and ammonium in drinking waters from Medias region (Medias, Copsa Mica towns and Tarnava village) and to investigate the health risk associated with the consumption of drinking water contaminated with these compounds. The health risk was calculated using chronic daily intake, hazard quotient and total hazard quotient. High concentrations of nitrite, nitrate and ammonium were found, at least one of the nitrogen compounds exceeding the maximum allowable concentrations (0.5 mg/L NO2-, 0.5 mg/L NH4+, 50 mg/L NO3-) in about half of the analysed samples. Generally, the chronic daily intake values were lower for nitrite and ammonium than for nitrate. The hazard quotients for nitrate were higher than the critical unity value, indicating that the consumption of contaminated waters from Tarnava village and Medias town may cause potential non-carcinogenic risk. Moreover, for the same samples, the total hazard quotients were higher than the critical unity value, suggesting that potential adverse health effects may appear after the consumption of drinking water.